A AVALIAÇÃO DE PROGRAMAS DA CAPES, OS CONCEITOS E O USO DE INDICADORES BIBLIOGRÁFICOS - Sandro Vieira Soares (Universidade Federal de Santa Catarina, 2015)
The need to evaluate graduate programs’ performance due to their capacity to add knowledge ratified by the scien tific community is well accepted and understood. This paper aims to investigate the impact of the use of bibliographic production’s indicators in the groupi ng of graduate programs in the Business, Accounting and Tourism knowledge area in the period of 2010 - 2012. The results revealed that grouping programs based on clusters analysis resulted in highly distinct clusters in terms of both their qualitative and qu antitative composition. Groups 1, 2, 3, 4 and 5 were formed by 8, 3, 3, 13 and 50 programs, respectively. Programs with Master and PhD degrees were mainly allocated to groups 1, 3 and 4 and programs with only Master degree have been allocated in the cluste r 5. The correspondence analysis identified that those groups are associated to their Capes’ grades. It was possible to identify that the program grade is only partially related to the composition of the clusters created using bibliographic indicators. Thu s, other assessment criteria as master and PhD formation and faculty, seem to have a relevant relative weight.